Localization of cystic fibrosis transmembrane conductance regulator mRNA in human fetal lung tissue by in situ hybridization. - McCray, P B (1992)
The fetal pulmonary epithelium secretes fluid. Cl transport is presumed to provide the driving force for net fluid secretion, although the cellular mechanisms have not been well identified in the fetus. The cystic fibrosis transmembrane conductance regulator (CFTR) is a cAMP- and nucleoside triphosphate-regulated Cl channel; mutations in CFTR cause cystic fibrosis. We hypothesized that if CFTR is involved in fetal lung fluid transport, the fetal pulmonary epithelium should express CFTR mRNA. We used the technique of in situ hybridization with 3H-anti-sense and, as a control, 3H-sense CFTR cRNA probes to localize CFTR mRNA in human fetal lung tissue and cultured lung explants and determine when in gestation it is expressed. Epithelial cells of both first and second trimester lung tissues expressed CFTR mRNA. A decreasing gradient of CFTR mRNA expression was present from the proximal to the distal pulmonary epithelium. Cultured second trimester lung tissue explants expressed more CFTR mRNA than the uncultured starting tissue, suggesting CFTR gene expression increased during the five days in culture. Furthermore, alveolar type II cells in cultured explants expressed CFTR mRNA, suggesting that these cells are Cl-secretory and may be involved in lung fluid transport. These data confirm that CFTR mRNA is expressed in the human fetal pulmonary epithelium, consistent with the Cl-secretory properties of the fetal lung.